Tinjauan Fikih Jinayah Terhadap Konsekuensi Zina dalam KUHP Tahun 1946 dan No. 01 Tahun 2023: A Review of Islamic Criminal Jurisprudence on the Consequences of Adultery in the 1946 Criminal Code and No. 01 of 2023 - Yasdin, Aditya Renaldi; Rapung, Rapung; Irsyad Rafi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to understand the Islamic perspective and the laws related to the definition of adultery, as well as a review of jinayah jurisprudence on the consequences of adultery in the Criminal Code of 1946 and No. 01 of 2023. This research is qualitative with a normative juridical approach, using library research methods by collecting books or references related to the research. The results show that, first, adultery in the perspective of jinayah jurisprudence has a different definition from Article 284 of the 1946 Criminal Code, which considers adultery as intercourse committed only by those who are married. Meanwhile, adultery according to Article 411 of the 2023 Criminal Code has the same meaning as the perspective of jinayah jurisprudence, which is intercourse committed by those who are either married or unmarried. Second, the review of jinayah jurisprudence on the consequences of adultery in the 1946 Criminal Code and No. 01 of 2023 is not accepted, because the imposition of sanctions for the crime of adultery must consider stronger evidence. Jinayah jurisprudence differentiates the consequences of adultery into two: stoning for those who are married, and one hundred lashes and one year of exile for those who are not married. The 1946 Criminal Code punishes perpetrators of adultery with a maximum prison sentence of 9 months for those who are married. Meanwhile, Article 411 does not differentiate the marital status of the perpetrator and punishes with a maximum prison sentence of 1 year or a fine of up to 10 million rupiahs. In the case of cohabitation, the penalty is a maximum of 6 months in prison or a fine of up to 10 million rupiahs. If adultery is committed with a family member, the prison sentence can reach 10 years. This research provides insights for students and the public about the limits and legal consequences of adultery from the perspective of jinayah jurisprudence and the Criminal Code.